„Mittatur senex in scholas” – opinie Seneki Retora o retorach, sztuce wymowy i jej nauczaniu w praefationes ksiąg „Oratorum et rhetorum sententiae, divisiones, colores” - Nowak, Magdalena (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
Each of the 11 books of Seneca Rhetor’s Oratorum et rhetorum sententiae, divisiones, colores is premised with a praefatio, although not all of them survived or survived intact. The author uses praefationes to mention famous contemporary rhetors, orators and the system of cultivating the art of rhetoric. The information about Roman rhetoric included in praefationes is being analyzed in the article in order to answer the following question: what picture of rhetoric and why did Seneca painit for his sons, the recipients of his work?

Lucius Annaeus Seneca Rhetor, living in the 1st century A.D., was the author of a work entitled Oratorum et rhetorum sententiae, divisiones, colores. Seneca dedicated his work to his three sons: Seneca Philosophus, Novatus and Mela. It was supposed to help them in learning the art of rhetoric. Seneca’s work consists of 11 books, 10 of them include controversiae, i.e. declamations in a form of court speeches and one contains suasoriae – advisory speeches. Each book of controversiae is premised with praefatio written in a form of a letter to the sons (praefations to books 5, 6 and 8 have not been preserved and praefatio to book 9 is incomplete). In each praefationes Seneca mentions and describes great orators, to whom he used to listen when he was young. In praefationes, apart from his memoirs about rhetors, there are also the author’s opinions about kinds of trainings at schools of rhetoric, the educational system and the level of oratory art education. This information, as well as Seneca’s respective assessments and opinions prove that praefationes were supposed to be not only an introduction to each book or the work linking element. One can also find in praefationes a specific compendium of knowledge concerning rhetoric of the Early Empire Period. The subject of this paper presents, on the basis of praefationes, Seneca’s opinions about the art of oratory and its teaching, how he explained changes in the Roman rhetoric: which phenomena in contemporary art of oratory, as well as which features and virtues of the orators in question, he found positive and worth following and which he criticized: how he presented and expressed his own opinions for the purpose of convincing his work’s addressees – his sons – of his views.
Mittatur senex in scholas – Seneca Rhetor’s opinions on rhetors, art of oratory and its teaching in praefationes of 'Oratorum et rhetorum sententiae, divisiones, colores books'
Keywords: Seneca Rhetor; declamation; controversiae; suasoriae; praefatio; Roman rhetoric